The relationship between office automation system and employee's productivity in UiTM Machang Kelantan/ Noor Ayu Mohd Daud - Mohd Daud, Noor Ayu (2013)
The title for this study is the relationship between office automation system and employee's productivity in UiTM Machang, Kelantan. The purpose of this study was to identify the relationship between office automation system and employee's productivity in UiTM Machang Kelantan. Besides that, this study also want to determine the level of employee's productivity when using office automation system. The data were gathered through the questionnaire distributed to the employees of UiTM Machang, Kelantan and 60 respondents were chosen randomly in order to determine the relationship between office automation system and employee's productivity in UiTM Machang, Kelantan and only 47 questionnaires were usable for futher analysis. The study was found that there is a relationship between office automation system and employee's productivity.